The late Paleozoic Ice Age along the southwestern margin of Gondwana: Facies models, age constraints, correlation and sequence stratigraphic framework. (April 2021) - López-Gamundí, Oscar; Limarino, Carlos O.; Isbell, John L.; Pauls, Kathryn; Césari, Silvia N.; Alonso-Muruaga, Pablo J.
Abstract: The southwestern margin of South America offers a complete record of the Late Paleozoic Ice Age (LPIA) that affected the Gondwana supercontinent. The tripartite division of LPIA glacial episodes has been refined with the help of new radiometric dates and biostratigraphic (flora and fauna) zonations in recent years to five shorter-lived discrete events: 1. Latest Devonian-earliest Tournaisian, 2. Tournaisian, 3. Visean, 4. Serpukhovian-Early Bashkirian, 5. late Pennsylvanian-earliest Permian. These glacial events are capped by postglacial transgressive deposits with marine fauna. The unbalanced preservation potential of the glacial deposits, skewed toward the glaciomarine sediments, provides an uneven stratigraphic record with few cases of continental glacial sedimentation, confined to the Serpukhovian-Early Bashkirian event, and numerous examples of glacial sedimentation in marine environments. Glacial sedimentation in marine settings has been grouped in two main facies associations: a valley-glacier-retreat (fjord) facies association and a submarine-retreat (glaciomarine apron) facies association in open-marine areas. Transitional facies, correspondent to those formed by the flooding of valleys during postglacial transgressions, are widely distributed along the Protoprecordillera in western Argentina, where paleofjord successions are well exposed particularly in western Paganzo Basin, and mapped in subsurface in the Tarija basin. A general paleofjord model includes (from base to top) the following stages: (i) Incision of paleovalley and deposition of subglacial diamictites in ice contact deltas, (ii) Early Transgressive stage characterized by resedimentation of subglacial material by subaqueous sediment gravity flows and slumps in proglacial settings, (iii) Maximum flooding (late transgressive stage) dominated by black shales or laminated mudstones related to a marine incursion that flooded valleys; normal marine or brackish conditions may dominate this stage and (iv) Highstand: progradation of a fluvial-deltaic system including in some cases Gilbert-type deltas. In glaciomarine apron environments, the basal facies includes massive clast-supported conglomerates, with few striated and polished clasts, followed by fining-upward successions including thinly bedded diamictites with ice-rafted debris (IRD) and locally contorted sandstone masses in diamictite beds, indicative of mass-emplacement mechanisms. The presence of inter- and intratill pavements suggests glacial advance/retreat fluctuations along the basin margins. Deglaciation sequences, reflecting deposition mainly during the retreat of ice sheets, ice caps and alpine glaciers and successive deglaciation, can be used as operational tools for the analysis of glacial successions in southwestern Gondwana. They are characterized as rather simple upward-fining successions in open marine settings as exemplified in most of the Calingasta-Uspallata Basin, Claromecó Basin (and adjacent Ventana foldbelt, VFB) and central portions of the Paraná and Karoo basins. In more proximal areas (i.e., paleofjords) this vertical trend is commonly punctuated with deltaic wedges fed by nearby provenance areas. The late Paleozoic glacial-related successions of southwestern Gondwana exhibit a common tripartite motif, equivalent to second-order sequences with estimated durations of 10–80 Myr. The lower section corresponds to glacial and glacially-influenced diamictites; the middle interval is initiated with postglacial transgressions. The lower and middle intervals correspond to the deglaciation sequence as described and identified in several basins of Gondwana. Finally, the upper term includes coastal progradation, followed in some places by continentalization, accompanied in many sectors by increasing aridization. Examples of second-order sequences can be identified in the thick late Paleozoic successions of the Paraná and Karoo basins and in the VFB. Thinner second order sequences can be identified in the Calingasta-Uspallata, Rio Blanco, Paganzo and San Rafael basins. In the Paganzo and San Rafael basins the middle interval is also punctuated by short lived marine ingressions. The basal sequence boundary is commonly an abrasion surface (glacial erosion surface, GES) developed on bedrock. Deglaciation sequences are assigned to third order sequences made up, when present, of a thin lowstand system tract (LST) of subglacial deposits followed upward by thick glaciomarine and glacially influenced sediments. These facies are part of a thick transgressive systems tract (TST) that culminates with marine shales that reflect interglacial or postglacial conditions during ice retreat. Thus, the deglaciation sequences are proposed to be third order sequences made up of LST-TST or exclusively TST. Highlights: LPIA (Late Paleozoic Ice Age). SW Gondwana basins. Facies models. Biozones. Sequence stratigraphy.